Requirements on synthesis gas from gasification for material and energy utilization: a mini review - Leuter, Philipp; Fendt, Sebastian; Spliethoff, Hartmut (Frontiers in Energy Research, 2024)
Achieving sustainable energy and material use mandates a critical focus on carbon recycling. The imperative for an efficient carbon cycle is paramount in sustainable energy systems and the chemical industry. Syngas, derived from waste and biomass gasification, offers a robust foundation for such recycling efforts. Various technologies, each with unique gas purity requirements, facilitate further refinement of syngas. This study provides a detailed and comparative analysis of the purity specifications necessary for both energetic and material utilization pathways.